The identification of vat dyes on cellulosic materials - Derrett-Smith, D. A.; Gray, John, 1922- (Pergamon Press, 1967)
The Identification of Vat Dyes on Cellulosic Materials focuses on the determination of the dyeing class of all the dyes usually found on cellulosic materials, which is a another method of distinguishing between reactive and other classes of dyes on these materials. This book discusses the characteristics of vat and soluble vat dyes. Organized into six chapters, this book starts with an overview of the various methods of preparing the five reagents used in the tests, namely, alkaline hydrosulfite, acid hydrosulfite, nitric acid, sulfuric acid, and acid potassium permanganate. This text then des.